1984
DOI: 10.1017/s0022112084002366
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase flow equations for a dilute dispersion of gas bubbles in liquid

Abstract: Equations of motion correct to the first order of the gas concentration by volume are derived for a dispersion of gas bubbles in liquid through systematic averaging of the equations on the microlevel. First, by ensemble averaging, an expression for the average stress tensor is obtained, which is non-isotropic although the local stress tensors in the constituent phases are isotropic (viscosity is neglected). Next, by applying the same technique, the momentum-flux tensor of the entire mixture is obtained. An equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
98
0
5

Year Published

1985
1985
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(106 citation statements)
references
References 11 publications
1
98
0
5
Order By: Relevance
“…Since we are expressing P 12 1 in terms of T 12 1 , the momentum equation for V 1 1 is reduced to a first-order differential equation. Therefore, no boundary conditions for this equation need to be specified at the channel walls.…”
Section: Approximate Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Since we are expressing P 12 1 in terms of T 12 1 , the momentum equation for V 1 1 is reduced to a first-order differential equation. Therefore, no boundary conditions for this equation need to be specified at the channel walls.…”
Section: Approximate Modelmentioning
confidence: 99%
“…Finally, a boundary condition for T 1 1 , and using the limiting expression for thermal conductivity for dilute particulate systems ͓k = ͑225 ͱ / 576͒T 1/2 ͔, we obtain a relatively simple approximate boundary condition given by…”
Section: -15mentioning
confidence: 99%
See 1 more Smart Citation
“…In the data available the percentages of gas are unknown, yet important according to the present model! Conservation of momentum (gas bubbles) BIESHEUYEL et al [3] gives :…”
mentioning
confidence: 99%
“…The equation of motion of this new variable leads to a non-dilute form of the Rayleigh-Plesset equation. Our [5,6] or cell models [7,8] (5) and (7), and the RayleighPlesset equation (1) [1][2][3][4] for the rotating motion Vg = n x r, and it may also be compared to the internal momentum appearing in the motion of the bubble with a velocity w relative to the liquid. In fact the study of the motion of a rigid particle in a perfect fluid has already shown that the equations of motion are most elegantly rewritten using an overall internal momentum or angular momentum [ 16,17].…”
mentioning
confidence: 99%